Helianthemum (sect. Helianthemum) raskebdanae (Cistaceae), a new species from northeastern Morocco - Alonso-Vargas, Mª Angeles; Crespo, Manuel B.; Juan, Ana; Sáez, Llorenç (Phytotaxa, 2015)
A new species, Helianthemum raskebdanae (H. sect. Helianthemum), is described from the maritime cliffs of north-eastern Morocco. It is easy to identify because of its glabrous and fleshy leaves with swollen reddish pulvinules at the petiole base, glabrous sepals with only minute stellate hairs on one margin, and large pinkish to purple petals. The new species is only known from three small, isolated sites, and it is here considered as Endangered (EN). Although it superficially resembles the Algerian H. maritimum, its combination of character-states is not found in the latter nor in any other related species of the section, i.e. H. apenninum, H. dianicum, H. scopulicola and H. virgatum, which warrants its recognition at the species rank. Micromorphological data support the proposed taxonomic treatment. Furthermore, nomenclatural types are designated for H. maritimum and H. maritimum f. albiflorum, two close Algerian relatives.